2017
DOI: 10.1016/s1002-0160(17)60382-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Soil Fertility and Plant Nutrient Management in Tropical Agro-Ecosystems: A Review

Abstract: The greatest challenge for tropical agriculture is land degradation and reduction in soil fertility for sustainable crop and livestock production. Associated problems include soil erosion, nutrient mining, competition for biomass for multiple uses, limited application of inorganic fertilizers, and limited capacity of farmers to recognize the decline in soil quality and its consequences on productivity. Integrated soil fertility management (ISFM) is an approach to improve crop yields, while preserving sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 49 publications
2
66
1
2
Order By: Relevance
“…The major mechanisms responsible for these improvements are thought to be the formation of organo-Al complexes that render the Al less toxic or direct neutralization of Al from the increase in pH caused by the organic matter. The possible alternative of using organic sources such as crop residues, manures, compost and biochar are substitutes for lime (Agegnehu and Amede, 2017). The authors demonstrated that organic sources raises pH and precipitate Al in direct proportion to its basic cation or ash alkalinity with a correction for the acidity produced during the oxidation of the N in the material.…”
Section: C) Addition Of Organic Fertilizers To Acidic Soilsmentioning
confidence: 99%
“…The major mechanisms responsible for these improvements are thought to be the formation of organo-Al complexes that render the Al less toxic or direct neutralization of Al from the increase in pH caused by the organic matter. The possible alternative of using organic sources such as crop residues, manures, compost and biochar are substitutes for lime (Agegnehu and Amede, 2017). The authors demonstrated that organic sources raises pH and precipitate Al in direct proportion to its basic cation or ash alkalinity with a correction for the acidity produced during the oxidation of the N in the material.…”
Section: C) Addition Of Organic Fertilizers To Acidic Soilsmentioning
confidence: 99%
“…On the other hand, organic amendments are often not available on farm at the amounts required (Agegnehu and Amede 2017). The best alternative is integrating organic and mineral fertilizers for tackling soil fertility depletion and sustainably increasing crop yields (Agegnehu and Amede 2017;Getachew et al 2014b;Gete et al 2010).…”
mentioning
confidence: 99%
“…Due to high demographic growth in West Africa, the demand for crop and livestock products is rapidly increasing, leading to the expansion of croplands onto rangelands, thereby constraining livestock mobility, see for instance in Burkina Faso (Vall et al, 2006). Consequently, the number of livestock and corresponding organic matter production are decreasing with a serious risk of soil fertility and crop productivity decline, as already pointed out by Pieri (1989), Lericollais (1999) and more recently by Agegnehu and Amede (2017). Two strategies to maintain livestock activities are commonly observed.…”
Section: Purposementioning
confidence: 96%